Failure mechanisms of intermetallic compounds in aluminum-steel resistance spot welds utilizing advanced electron microscopy techniques - Shuai Wang; Zhongjie Yuan; Yufeng Meng; Binghui Ge (Journal of Materials Research and Technology)
The formation of hard and brittle intermetallic compounds (IMCs) significantly impacts the mechanical properties of welded joints. In this study, three-point bending tests were conducted on aluminum-steel resistance spot welding (RSW) joints, and the failure mechanism of the IMCs was studied by using advanced electron microscopy. Our findings revealed that the Al13Fe4, Al5Fe2 and Al12Fe3Si phases exhibited distinct plastic deformation mechanisms during the test, and cracks initiated and propagated close to these phases, ultimately leading to the joints' failure. Our work contributes to a deeper understanding of the failure mechanisms of IMCs in aluminum-steel RSW joints.